2016
DOI: 10.4132/jptm.2016.03.09
|View full text |Cite
|
Sign up to set email alerts
|

Non-small Cell Lung Cancer with Concomitant <i>EGFR</i>, <i>KRAS</i>, and <i>ALK</i> Mutation: Clinicopathologic Features of 12 Cases

Abstract: Background:Although epidermal growth factor receptor (EGFR), v-Ki-ras2 Kirsten rat sarcoma viral oncogene (KRAS), and anaplastic lymphoma kinase (ALK) mutations in non-small cell lung cancer (NSCLC) were thought to be mutually exclusive, some tumors harbor concomitant mutations. Discovering a driver mutation on the basis of morphologic features and therapeutic responses with mutation analysis can be used to understand pathogenesis and predict resistance in targeted therapy. Methods:In 6,637 patients with NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 27 publications
5
79
2
Order By: Relevance
“…Associated evidence items provide a brief description of the clinical relevance, links to CIViC evidence items, and associated citations. An illustrative output report that displays most OpenCAP features, including CIViC variant descriptions and CIViC assertions, was created using a previously reported patient from the literature 27 (Data Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…Associated evidence items provide a brief description of the clinical relevance, links to CIViC evidence items, and associated citations. An illustrative output report that displays most OpenCAP features, including CIViC variant descriptions and CIViC assertions, was created using a previously reported patient from the literature 27 (Data Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…The coexistence of mutations in a patient may be a consequence of intratumoral heterogeneity due to coexisting divergent clones within the same tumor. 49,50 Tumors with EGFR and KRAS co-positivity generally show histologic features typical of EGFR positive cases (predominant acinar pattern). 49 Similarly, 3 of our 4 cases with dual positivity had acinar histology.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Tumors with EGFR and KRAS co-positivity generally show histologic features typical of EGFR positive cases (predominant acinar pattern). 49 Similarly, 3 of our 4 cases with dual positivity had acinar histology. Further, it has been hypothesized that presence of coexisting mutations is associated with an aggressive disease profile with suboptimal response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC prior to treatment, the majority of oncogenic driver mutations are mutually exclusive with other mutations [5,6]. However, recent studies have shown that additional driver mutations such as KRAS, ALK, and PI3K mutations co-exist with EGFR-mutations in a certain percentage of lung cancers [5,[7][8][9][10][11][12][13][14]. Of note, these driver mutations have been found not only in different cell populations in tumors, but also within the same cell population [15,16].…”
Section: Introductionmentioning
confidence: 99%